2008
DOI: 10.1080/10401330802199617
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Academic Medicine: A Good Pipeline of Women Graduates Is Not Advancing

Abstract: More women are applying, enrolling and graduating from the University of Split School of Medicine. Women also perform statistically better on entrance exam and have better graduation grades, yet they remain a minority in faculty and leadership positions. A review of county-wise employment statistics revealed that women were more frequently unemployed and less likely to specialize in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
0
18
1
1
Order By: Relevance
“…Based on the analysis of a selection system at the end of the third academic year, these observations do not quite corroborate the data in the literature showing a more stable trajectory for female than for male students 10 . Bearing in mind that the selection process increases competition, some authors have shown that female students have higher anxiety than male students and are more motivated to achieve their goals.…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Based on the analysis of a selection system at the end of the third academic year, these observations do not quite corroborate the data in the literature showing a more stable trajectory for female than for male students 10 . Bearing in mind that the selection process increases competition, some authors have shown that female students have higher anxiety than male students and are more motivated to achieve their goals.…”
Section: Introductioncontrasting
confidence: 70%
“…Thus, over the past few decades, European medical studies have seen a significant feminisation of the profession. Certain studies have observed a more stable trajectory for female than for male students 5 , 10 . Generally, these studies have reported that female students have a more positive attitude towards academic work than male students.…”
Section: Introductionmentioning
confidence: 97%
“…Our promotional activity did not affect gender ratio. The predominance of women applicants has been present since the founding of the School of Medicine in Split (12).…”
Section: Discussionmentioning
confidence: 99%
“…This section would have several purposes as follows: (i) to nurture scientist-citizens who can participate effectively in discussions about issues in science and society; (ii) to increase dialogue between scientists, the public, and policymakers, (iii) to promote multidisciplinary interaction among scholars in our community about complex science policy problems, and (iv) to expand public understanding of science. This section could harbor articles similar to the recent editorial by Petrovečki et al (1) or to the two recently published articles by our group (4,5). When the discussions about science policy are published in a peer-reviewed journal, they assume a higher level of importance and significance.…”
Section: Wanted: Venue For Science Policy Discussionmentioning
confidence: 99%